2012
DOI: 10.1259/dmfr/14555883
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic biomonitoring in oral mucosa cells following dental X-ray

Abstract: Objectives: In the past decades, X-rays have been used widely for diagnosis in dentistry. However, it is well known that ionizing radiation causes damage (including single-and double-strand breaks) to deoxyribonucleic acid (DNA) and DNA-protein crosslinks, and induces cellular death. Therefore, outlining the cytogenetic effects induced by X-ray is necessary to identify the degree of cancer risk and minimize potential risks to patients and clinicians. To date, a variety of assays have been proposed in cytogenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…3 Theoretically, the biological effects of dental panoramic exposure can damage cells through oxidative reaction, including the formation of micronucleus. 4,5 A micronucleus is often employed as a biomarker of chromosomal damage that, in its early stages, contributes to carcinogenesis. 6 Research has confirmed the increase in micronucleus after conventional panoramic radiograph exposure which has a correlation with 8-oxo-dG expression as a marker of DNA adduct.…”
Section: Research Report Introductionmentioning
confidence: 99%
“…3 Theoretically, the biological effects of dental panoramic exposure can damage cells through oxidative reaction, including the formation of micronucleus. 4,5 A micronucleus is often employed as a biomarker of chromosomal damage that, in its early stages, contributes to carcinogenesis. 6 Research has confirmed the increase in micronucleus after conventional panoramic radiograph exposure which has a correlation with 8-oxo-dG expression as a marker of DNA adduct.…”
Section: Research Report Introductionmentioning
confidence: 99%
“…Nowadays the lesions detection and disease diagnosis are based on clinical and paraclinic findings. In the past decades, x-rays have been used widely in dentistry (1). Dental radiology is being extensively used especially after the consolidation of the dental implant technique (2).Therefore radiographic findings play an important role.…”
Section: Introductionmentioning
confidence: 99%
“…These studies, however, all reported increases in other nuclear alterations (e.g. pyknosis, karyorrhexis and karyolysis) that are associated with increased cytotoxicity [63][64][65][66] . Recently, Preethi et al (2016) reported significant increases in the number of micronucleated cells in BMCs after dental radiography in paediatric patients 62 .…”
Section: Discussionmentioning
confidence: 95%